PERGESERAN MAKNA BUDAYA ONDEL-ONDEL PADA MASYARAKAT BETAWI MODERN - Paramita, Sinta (Jurnal Bakti Masyarakat Indonesia, 2019)
Ondel-ondel is a giant puppet that is seen by the Betawi people as a sacred culture and is used for ritual offerings to ancestral spirits. Culture is defined as the order of knowledge, experience, beliefs, values, attitudes, meanings and is passed on from generation to generation, through individual and collective efforts, an example being the ondel-ondel culture in Betawi village, Pacar-Senen road, Central Jakarta. Ondel-ondel is a Betawi folk cultural performance passed down from generation to generation. However, as the age progresses, ondel-ondel is no longer a sacred object and is no longer used for ritual offerings. Ondel-ondel today serves no purpose other than decoration or used for the livelihoods of the Betawi people. From the above phenomenon, the researcher wants to describe the shift in the meaning of ondel-ondel culture in the modern Betawi community, by using a qualitative case study method, the researcher tries to find out how the meaning has shifted.The results of observations and discussions in this study are that the Betawi people are experiencing social and economic problems. Therefore, thinking creatively, they turn ondelondel into something interesting for general audience. Raspel (Ondel-ondel Community) are trying to invite unemployed teenagers and adults, to make use of their time by doing ondel-ondel shows, rather than being idle or doing committing crime. By turning ondel-ondel into an attractive commodity, Raspel hopes to improve the standard of living of the Betawi people. However, many other ondel-ondel communities turn ondel-ondel into mere street entertainment, which makes ondel-ondel underestimated by the public. Raspel hopes that ondel-ondel culture will continue to be communicated attractively, so that the general audience can enjoy ondel-ondel properly ABSTRAK: Ondel-ondel merupakan sebuah boneka raksasa yang dimaknai masyarakat Betawi sebagai budaya yang sakral dan digunakan untuk ritual persembahan kepada roh-roh leluhur. Budaya didefinisikan sebagai tatanan pengetahuan, pengalaman, kepercayaan, nilai, sikap, makna dan diwariskan dari generasi ke generasi, melalui usaha individu dan kelompok. Seperti budaya ondel-ondel yang ada di kampung Betawi, Jalan Pacar-Senen, Jakarta Pusat. Ondel-ondel merupakan pertunjukan budaya rakyat Betawi diwariskan secara turun-temurun dari generasi ke generasi. Namun demikian, Seiring dengan perkembangan jaman ondel-ondel sudah tidak lagi menjadi benda yang sakral dan juga tidak lagi digunakan untuk ritual persembahan. Ondel-ondel masa kini tidak lebih hanya dijadikan hiasan atau digunakan untuk matapencarian masyarakat Betawi. Dari fenomena di atas peneliti ingin menjabarkan pergeseran makna budaya ondel-ondel pada masyarakat Betawi Modern, dengan menggunakan metode kualitatif studi kasus, peneliti berupaya mengetahui bagaimana pergesaran makna tersebut. Hasil observasi dan diskusi dalam penelitian ini adalah masyarakat Betawi mengalami permasalahan dibidang sosial dan ekonomi yang menimpa mereka. Oleh sebab itu mereka berfikir kreatif, salah satunya dengan mengemas ondel-ondel menjadi sesuatu yang menarik untuk masyarakat luas. Raspel (Komunitas ondel-ondel) mereka berupaya mengajak para remaja dan dewasa yang belum memiliki pekerjaan, untuk memanfaatkan waktunya dengan melakukan pertunjukkan ondel-ondel, dibandingkan hanya berdiam diri atau melakukan hal-hal negatife. Dengan mengemas ondel-ondel menjadi bahan komuditas yang menarik, Raspel berharap dapat meningkatkan taraf hidup masyarakat Betawi. Namun banyak komunitas ondel-ondel lain, membuat ondel-ondel menjadi hiburan jalanan, Hal tersebut yang membuat ondel-ondel dipandang sebelah mata oleh masyarakat. Raspel berharap budaya ondel-ondel tetap dikomunikasi secara menarik, sehingga masyarakat luas dapat menikmati ondel-ondel secara yang baik.